2017
DOI: 10.1101/gr.206938.116
|View full text |Cite|
|
Sign up to set email alerts
|

Detecting differential copy number variation between groups of samples

Abstract: We present a method to detect copy number variants (CNVs) that are differentially present between two groups of sequenced samples. We use a finite-state transducer where the emitted read depth is conditioned on the mappability and GC-content of all reads that occur at a given base position. In this model, the read depth within a region is a mixture of binomials, which in simulations matches the read depth more closely than the often-used negative binomial distribution. The method analyzes all samples simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 63 publications
(57 reference statements)
2
31
0
Order By: Relevance
“…S6). This region includes two indels from this study: LP3621 and Cnv770, which encode a 16 bp and a 107 bp deletion in the freshwater and marine haplotypes, respectively (Lowe et al 2018). Genetic manipulations are now underway to test whether this intronic region contains one or more enhancers active near developing lateral plates or neuromasts, and if so, to test which SNPs or indels may alter the activity of these enhancers and drive the phenotypic differences in plate number, neuromast number, and neuromast patterning.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…S6). This region includes two indels from this study: LP3621 and Cnv770, which encode a 16 bp and a 107 bp deletion in the freshwater and marine haplotypes, respectively (Lowe et al 2018). Genetic manipulations are now underway to test whether this intronic region contains one or more enhancers active near developing lateral plates or neuromasts, and if so, to test which SNPs or indels may alter the activity of these enhancers and drive the phenotypic differences in plate number, neuromast number, and neuromast patterning.…”
Section: Discussionmentioning
confidence: 98%
“…2005; Lowe et al. 2018) (See Table S1 for details of PCR primers and genotyping assays). Fish were also genotyped for a marker in the 3′ UTR (untranslated region) of the isocitrate dehydrogenase gene ( Idh ) that distinguishes males from females (Peichel et al.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…S8). Notably, TG-repeats are enriched in other loci that have undergone recurrent ecotypic deletions during marine-freshwater stickleback evolution (31) (table S2, fig. S9), and near DNA breakage sites in humans (fig.…”
Section: Main Textmentioning
confidence: 99%
“…In this example, the occurrence of a deletion at this fragile site was estimated to be approximately 10 4 times more likely than a point mutation and thus may point to a type of alternative mechanism to standing genetic variation for repeated and rapid freshwater adaptation, though a genomic survey of the general importance of this type of mutation has been hampered by difficulties in sequencing through repetitive regions (and thus is an area where future long-read sequencing may prove particularly useful). Similarly, dynamic copy number variation and movement of transposable elements may provide another pathway for repeated freshwater adaptation (31), and Lowe et al (94) found consistent differences in copy number variation between oceanic and freshwater ecotypes using the same stickleback genomes sequenced by Jones et al (84). However, the extent to which such variation actually contributes to repeated stickleback adaptation as opposed to neutrally hitchhiking on adaptive haplotypes is still uncertain.…”
Section: Other Molecular Mechanisms Driving Contemporary Evolutionmentioning
confidence: 99%